Distribution in Islamic Economic Perspective (Critics to Capitalist) - Telsy Fratama Dewi Samad (IAIN Manado, 2019)
Distribution is one of the economic topics that is necessary to be discussed, mainly the distribution of wealth because it concerns the effort to achieve prosperity for all levels of society in a country through equitable distribution of wealth. In this article, we will discuss the concept of wealth distribution both from conventional perspective, which is based on capitalist ideology and from the perspective of Islamic economics. As the public understanding about capitalism, it is one of the economic comprehension carried by the Father of Economics